Affect and Emotions in Two Chilean Postmemory Narratives: La dimensión desconocida by Nona Fernández and La resta by Alia Trabucco Zerán - Weldt-Basson, Helene C. (Revista Canadiense de Estudios Hispánicos)

(untitled) (Asociación Canadiense de Hispanistas, 2021)
La dimensión desconocida (2016) by Nona Fernández and La resta (2014) by Alia Trabucco Zerán are recent novels about the memory of the Augusto Pinochet dictatorship (1973-1990) in Chile that use emotions to reconstruct a historical era through memory. The two novels share an emphasis on the affect and emotions of both readers and characters. While La dimensión desconocida is a historical novel that invites the reader to identify and empathize with the protagonists, La resta is an allegorical novel that provokes the reader to think about history by startling him or her through the narration of the protagonists' violent games.